Proceedings of the Proceedings of the 3rd International Conference on Environmental Risks and Public Health, ICER-PH 2018, 26-2 2019
DOI: 10.4108/eai.26-10-2018.2288913
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Nutrient Intakes, Nutritional Status, and Menstrual Disorders of Adolescent Girls at Islamic Boarding School in Bone District

Abstract: Both under-and over-nutrition problems exist among Indonesian adolescent girls which was around 7.5% at aged 16-18 years was thin, and 5.7% was obese. The problem of the menstrual disorder is also common among adolescent girls as 13.5% of Indonesian women aged 10-59 years had an irregular menstrual cycle. This research aims to investigate the relationship between nutritional status and macronutrient intake and menstrual disorders at adolescent girls. The study design was a cross-sectional with chisquare test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…There was no significant association of both carbohydrate and protein intake with menstrual disorder. It was found that many adolescents with adequate and excess carbohydrate and protein intake also experienced the menstrual disorder [ 23 ]. The previous study in a similar setting found a significant relationship between carbohydrate and menstrual disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant association of both carbohydrate and protein intake with menstrual disorder. It was found that many adolescents with adequate and excess carbohydrate and protein intake also experienced the menstrual disorder [ 23 ]. The previous study in a similar setting found a significant relationship between carbohydrate and menstrual disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An energy deficit diet has shown to increase the chances of irregularities in menses, possibly because of less intake of dietary fat, hormone synthesis and regulation is hindered in the body. A similar study among adolescents also showed that girls that had a low intake of dietary fat had higher chances of getting menstrual disorders and no relationship existed between fat and carbohydrate intake with the same (Indriasari et al, 2019). Another possible relation could be between the hypothalamic-pituitary-ovarian axis and a mild restriction in calorie intake which created a negative energy balance in the body (Kapil & Sachdev, 2012).…”
Section: Diet Qualitymentioning
confidence: 91%
“…Status gizi pada perempuan remaja dan dewasa awal dapat ditentukan berdasarkan beberapa indikator, seperti Indeks Massa Tubuh (IMT), Persen Lemak Tubuh (Body Fat; BF), dan Lingkar Pinggang (LP). Pada beberapa penelitian, indikator status gizi yang terbukti berhubungan dengan terjadinya gangguan menstruasi adalah BF dan LP, sedangkan IMT ditemukan tidak berhubungan dengan gangguan menstruasi (Khaerunisa, et al 2018;Thakur, et al 2018;Indriasari, et al 2018). Khaerunisa, et al (2018 menjelaskan bahwa jaringan lemak sangat menentukan proses pembentukan hormon-hormon seksual.…”
Section: Hasil Dan Pembahasanunclassified
“…Namun demikian, beberapa penelitian lain yang telah dilakukan untuk menganalisis hubungan asupan zat gizi dan gangguan menstruasi menghasilkan kesimpulan yang tidak konsisten. Penelitian yang dilakukan Indriasari, et al (2018) hanya menemukan adanya hubungan pada asupan lemak, dimana hal ini pun tidak berhasil disimpulkan berdasarkan penelitian Khaerunisa, et al (2018). Asupan karbohidrat dan serat tidak ditemukan berhubungan dengan terjadinya gangguan menstruasi, kecuali untuk maltose (Houghton, et al 2018).…”
Section: Hasil Dan Pembahasanunclassified